Comparison of scald burns caused by hot water, tea and milk in preschool children - Basaran, Abdulkadir; Ozlu, Ozer (Annals of Medical Research, 2021)
Aim: Burn injury is an important health problem with physical, psychological and economic effects with children being affected the most. The aim of this study is to present the epidemiological and demographic data and clinical results of preschool pediatric patients with scald burns which are treated in a tertiary reference burn center.Materials and Methods: Preschool children admitted between January 2014 and August 2019 was included in the study. The demographic and epidemiological data, burn etiology, percentage of burned total body surface area and treatment results of patients were evaluated retrospectively from the patient files and the hospital registry.Results: A total of 1010 preschool children with scald burns were treated in our burn center from January 2014 to August 2019. Patients were grouped by the etiology as; group 1: water, group 2: tea and group 3: milk scalds. There were 628 patients in group 1, 304 in group 2 and 78 in group 3. The percentage of burned total body surface area was higher for scalds with milk and was found as 15.54±12.1 and the difference was statistically significant. The intensive care and the total hospital stay were also higher in scalds with milk. There were similar results with infection, grafting and mortality rates as being higher in the milk group. Conclusion: The majority of preschool patients in our burn center were scalds with water but the percentage of burned total body surface area, skin grafting and complication rates were higher in scalds with milk. Childhood burns were usually seen indoors at preschool period, necessitating training programs for family members supervising these children and raising the awareness of parents.
Keywords: Burn; complications; epidemiology; milk; scald; preschool children